One little lie [large type] - Coble, Colleen (Coble, Colleen. Pelican Harbor series, 2020)
After Jane Hardy is appointed sheriff in Pelican Harbor, Alabama, her father is arrested for theft and implicated in a murder. Jane quickly realizes that someone is out to destroy the only family she has. Fifteen years ago, she escaped with her father from a cult that her mother refused to leave. Has someone from that hoffible past found them? Meanwhile, documentary filmmaker Reid Dixon's latest project is covering Jane's career. Soon the two begin working together to clear her father. But Reid has his own secrets, and the gulf between them may be impossible to cross -- especially once her father's lie catches up with him.